2008
DOI: 10.2489/jswc.63.6.590
|View full text |Cite
|
Sign up to set email alerts
|

The Conservation Effects Assessment Project benchmark watersheds: Synthesis of preliminary findings

Abstract: The USDA has provided technical assistance and cost sharing to farmers and ranchers for implementing conservation practices on privately owned working lands since the 1930s. The primary purpose of the assistance programs has been to "improve the productivity of US farms and ranches and to protect the 'natural resource base' that sustained the agricultural enterprise" (Cox 2006). Conservationists have recognized for many years that these conservation programs protect millions of acres of farm and ranch lands fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 56 publications
0
59
0
Order By: Relevance
“…(Schilling et al 2007). The monitoring study results and the modeling findings reported here directly support the goals of the Conservation Effects Assessment Project, which seeks to evaluate the effectiveness of different conservation practices in mitigating water quality problems in a variety of watershed conditions across the United States (Richardson et al 2008;Duriancik et al 2008). The Squaw Creek watershed was designated as a control in the original monitoring study (Schilling and Spooner 2006).…”
Section: Figurementioning
confidence: 68%
“…(Schilling et al 2007). The monitoring study results and the modeling findings reported here directly support the goals of the Conservation Effects Assessment Project, which seeks to evaluate the effectiveness of different conservation practices in mitigating water quality problems in a variety of watershed conditions across the United States (Richardson et al 2008;Duriancik et al 2008). The Squaw Creek watershed was designated as a control in the original monitoring study (Schilling and Spooner 2006).…”
Section: Figurementioning
confidence: 68%
“…1). Understanding the headwater hydrology in this watershed is important because UBWC is one of 14 benchmark watersheds being studied as part of the US Department of Agriculture (USDA) Conservation Effects Assessment Project -Watershed Assessment Study (Richardson et al, 2008). Additionally, the findings from this study should be transferable to other headwater streams in cool humid climates.…”
Section: Study Sitesmentioning
confidence: 99%
“…Watershed models that can be used to evaluate the effects of climate and land use, particularly agricultural practices, on runoff and sediment from both upland fields and stream channels are essential to analyze erosion dynamics in an agricultural watershed. Watershed-scale models have been used in the US Conservation Effects Assessment Project (CEAP) (Richardson et al 2008) and the Canadian Watershed Evaluation of BMPs (WEBs) project (Yang et al 2007) to support BMP management and program evaluation. Since measured data at stream or field stations are often insufficient to distinguish sources of sediment within a watershed, models can be used to trace sediment sources and delivery in a watershed, and provide assistance to decision making in watershed management.…”
mentioning
confidence: 99%